Meibomian gland dysfunction: hyperkeratinization or atrophy?. Issue 1 (November 2015) - Jester, James; Parfitt, Geraint; Brown, Donald
Abstract Meibomian gland dysfunction (MGD) is the major cause of evaporative dry eye disease (EDED) and dysfunction is widely thought to mechanistically involve ductal hyperkeratinization, plugging and obstruction. This review re-evaluates the role of hyperkeratinization in MGD based on more recent findings from mouse models. In these studies, eyelids from normal young and old mice or mice exposed to desiccating stress were evaluated by immunofluorescent tomography and 3-dimensional reconstruction to evaluate gland volume, expression of hyperkeratinization markers and cell proliferation or stimulated Raman scattering (SRS) microscopy to assess lipid quality. Results indicate that aging mice show dropout of meibomian glands with loss of gland volume and a forward migration of the mucocutaneous junction anterior to the gland orifice; similar age-related changes that are detected in human subjects. Atrophic glands also showed evidence of epithelial plugging of the orifice without the presence of hyperkeratinization. Mice exposed to desiccating stress showed hyperproliferation of the meibomian gland and ductal dilation suggesting a marked increase in lipid synthesis. Lipid quality was also affected in EDED mice with an increase in the protein content of lipid within the duct of the gland. Overall, age-related changes in the mouse show similar structural and functional correlates with that observed in clinical MGD without evidence of hyperkeratinization suggesting that gland atrophy may be a major cause of EDED. The response of the meibomian gland to desiccating stress also suggest that environmental conditions may accelerate or potentiate age-related changes.